Analysis of the Influence of Population and Government Revenue on Poverty Levels in North Sumatra 2019-2023 - Manik, Salve Teresia Kristina; Nasha, Meilafayza; Sitompul, Agryani R; Silalahi, Johanna Dameria G; Pelawi, Deviona Caroline; Chairunisah, Chairunisah (Lembaga Riset Mutiara Akbar, 2024)
Poverty is one of the main challenges of development in Indonesia, including in North Sumatra Province. This province has a large and diverse population, with an uneven distribution between urban and rural areas. Based on the report of the Central Statistics Agency (BPS) of North Sumatra, the poverty rate in this region tends to fluctuate over the past five years (2019-2023). This study aims to analyze the effect of population and government revenue on the poverty rate in North Sumatra in 2019-2023. The main problem identified is the fluctuating poverty rate due to an increase in population without being balanced by adequate government revenue. This study uses a quantitative approach with analysis of variance (ANOVA) and SPSS software to process data. The results show that population has a low influence, while government revenue has a dominant influence in reducing poverty rates. The resulting model provides strategic direction for demographic and fiscal management to reduce poverty in North Sumatra.